Detection of Hepatozoon spp in naturally infected Brazilian dogs by polymerase chain reaction - de Sa, Alexandre Garcia; Figueiredo Cerqueira, Aloysio de Mello; O'Dwyer, Lucia Helena; Abreu, Fabricio da Silva; Ferreira, Renata Fernandes; Pereira, Ananda Mueller; Velho, Pedro Bittencourt; Rubini, Adriano Stefani; Pereira Almosny, Nadia Regina (Veterinary Solutions Llc, 2007)
Hepatozoon canis was molecularly identified in Rio de Janeiro State, Brazil. Twelve dogs from urban areas were studied by blood smear examination and the polymerase chain reaction (PCR) assay. From these dogs, only 1 was positive in both blood smears and PCR.
Keywords: dogs; ticks; hepatozoonosis; Hepatozoon canis; PCR; Brazil